2019
DOI: 10.35118/apjmbb.2019.027.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of glyphosate on various life stages of calanoid copepod, Pseudodiaptomus annandalei

Abstract: Copepods are one of the most important primary producers and biodiversity indicators. They are also highly susceptible to various toxicants. In this study, glyphosate (Roundup®), a widely used herbicide was used to investigate the toxicity effect on calanoid copepods, Pseudodiaptomus annandalei, focused on their nauplius, copepodid, and adult stages. Different concentrations of glyphosate (i.e. 0 - as control, 0.05, 0.1, 0.4, 1.6, 6.4 and 25.6 mg/L) were used to elucidate the tolerance level of P. annandalei. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…Information on rotifers is relatively limited (Appendix : Table S1), but our results are consistent with other studies of glyphosate toxicity on copepods, with notably greater sensitivity found in immature stages as compared to adults (Lim et al. 2019). While compelling evidence has accrued for acute and chronic toxicity in cladocerans at similar concentrations of glyphosate (e.g., ranges of LC 50 for Daphnia and Ceriodaphnia : 0.45–10.6 and 4.8–6.05 mg/L, respectively; Tsui and Chu 2003, Cuhra et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Information on rotifers is relatively limited (Appendix : Table S1), but our results are consistent with other studies of glyphosate toxicity on copepods, with notably greater sensitivity found in immature stages as compared to adults (Lim et al. 2019). While compelling evidence has accrued for acute and chronic toxicity in cladocerans at similar concentrations of glyphosate (e.g., ranges of LC 50 for Daphnia and Ceriodaphnia : 0.45–10.6 and 4.8–6.05 mg/L, respectively; Tsui and Chu 2003, Cuhra et al.…”
Section: Discussionsupporting
confidence: 91%
“…The general patterns of species turnover in communities exposed to glyphosate (alone or in combination) highlighted a stark contrast between sensitive rotifer (long-lasting declines at concentrations ≥0.3 mg/L) and copepod zooplankton (partial recovery over time, but none ≥5.5 mg/L), and highly tolerant cladocerans, with Alona, Chydorus, and Scapholeberis still thriving under severe glyphosate contamination, even in the presence of imidacloprid. Information on rotifers is relatively limited (Appendix S1: Table S1), but our results are consistent with other studies of glyphosate toxicity on copepods, with notably greater sensitivity found in immature stages as compared to adults (Lim et al 2019). While compelling evidence has accrued for acute and chronic toxicity in cladocerans at similar concentrations of glyphosate (e.g., ranges of LC 50 for Daphnia and Ceriodaphnia: 0.45-10.6 and 4.8-6.05 mg/L, respectively; Tsui andChu 2003, Cuhra et al 2013), such observations mostly rely on single-species cultures in a laboratory setting, with few to no studies using the most tolerant species found in our ponds.…”
Section: Community Responses To Agrochemicalssupporting
confidence: 91%
“…The general patterns of species turnover in communities exposed to glyphosate (alone or in combination) highlighted a stark contrast between sensitive rotifer (long-lasting collapse at concentrations ≥0.3 mg/L) and copepod zooplankton (partial recovery over time, but none ≥5.5 mg/L), and highly tolerant cladocerans, primarily belonging to Alona, Chydorus, and Scapholeberis (still thriving at 15mg/L of glyphosate, even in the presence of imidacloprid). Information on rotifers is relatively limited (Table S1), but our results are consistent with other studies of glyphosate toxicity on copepods, with notably greater sensitivity found in immature stages as compared to adults (Lim et al, 2019). While compelling evidence has accrued for acute and chronic toxicity in cladocerans at similar concentrations of glyphosate (Table S1; e.g., ranges of LC50 for Daphnia and Ceriodaphnia: 0.45-10.6 and 4.8-6.05 mg/L, respectively; Cuhra et al, 2013;Tsui & Chu, 2003), such observations mostly rely on single-species cultures in a laboratory setting, with few to no studies using the most tolerant species in our ponds.…”
Section: Community Responses To Agrochemicalssupporting
confidence: 91%
“…is even more resistant than the freshwater copepod A. robustus, for which the LC 50 is 19 ppm and 13 ppm in 24 h and 48 h, respectively [3]. This herbicide in its Roundup ® formulation also showed greater toxicity on the copepod Pseudodiaptomus annandalei (LC 50 11.7 ppm and 10.23 ppm in 24 and 48 h, respectively) [24] than on the ostracod observed in the current study. On the other hand, Eucypris sp.…”
Section: Discussionmentioning
confidence: 43%
“…Among herbicides, glyphosate is the most widely used in agriculture [22] in different formulations. Its effects in the aquatic environment have been reported for several species [3,23,24]. It induces a reduction in reproduction in the water flea Daphnia magna [25].…”
Section: Introductionmentioning
confidence: 99%